Strategies and instruments for active mobility: a European overview - D'Amico, Annunziata (TeMA - Journal of Land Use, Mobility and Environment, 2024)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always remaining in the groove of rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is the expression of continuously updating emerging topics concerning relationships between urban planning, mobility and environment, through a collection of short scientific papers written by young researchers. The Review Notes are made of four parts. Each section examines a specific aspect of the broader information storage within the main interests of TeMA Journal. In particular, the Urban strategies, programmers and tools section presents the different strategies and tools for active mobility implemented internationally. The purpose of this review is to provide an overview of the instruments and strategies implemented in Europe to encourage active mobility. In addition, some solutions to promote active transport implemented in several European cities have been reported. These initiatives represent an opportunity for European communities to act in a necessary, indispensable and continuous process of improving urban mobility in the direction of environmental sustainability. These measures, enhanced by dedicated tools such as SUMPs, promote behavioral change and support mobility planning, setting active mobility as a winning strategy to improve city life and urban efficiency.